Digital dark age : an overview for the humanities and social sciences - Migowski, Ana Lúcia; Justus Liebig University Giessen (My University, 2016)
The possibility of a Digital Dark Age worries computer scientists, archivists, and librarians, but it also concerns humanists and social scientists. The absence of access to digital data and cultural products due to the obsolescence of technologies used for today s communication, entertainment, work, production and circulation of scientific knowledge is an imminent risk. This report is based on texts and interviews with experts. Here we provide an overview of this emergent and urgent problem and present suggestions for prevention.
Keywords: digital preservation; humanities; social sciences; future of sciences; ddc:300